2020
DOI: 10.1021/acs.energyfuels.0c00226
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Chemical Inhibition Mechanism of DBHA on Free Radical Reaction during Spontaneous Combustion of Coal

Abstract: It is imperative to have an in-depth understanding of the chemical inhibition mechanism for spontaneous combustion of coal, not only for controlling and preventing spontaneous combustion of coal in the coal mining industry but also for reducing emissions of hazardous gases. N,N-dibenzylhydroxylamine (DBHA) as a hydroxylamine free radical scavenger can be chosen as a feasible stabilizer for the spontaneous combustion of coal. In this study, the inhibitory performance of DBHA was examined by investigating coal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…At 400°C, the g factor value of coal gangue reaches 2.008823 and the free radical concentration reaches 36.77 × 10 17 at 21% oxygen concentration, the free radical in the reaction system are generally in a high‐energy state, and the relaxation time is further prolonged. After free radical have been accumulated to a concentration enough for initiating the chain reactions of free radical, a large amount of heat is generated, bringing about a rapid increase in the ambient temperature, and finally causing spontaneous combustion of coal gangue 34,35 . Therefore, the spontaneous combustion of coal gangue is a process with the g factor value increasing, the free radical concentration rising, and the relaxation time lengthening (line width decreasing).…”
Section: Discussionmentioning
confidence: 99%
“…At 400°C, the g factor value of coal gangue reaches 2.008823 and the free radical concentration reaches 36.77 × 10 17 at 21% oxygen concentration, the free radical in the reaction system are generally in a high‐energy state, and the relaxation time is further prolonged. After free radical have been accumulated to a concentration enough for initiating the chain reactions of free radical, a large amount of heat is generated, bringing about a rapid increase in the ambient temperature, and finally causing spontaneous combustion of coal gangue 34,35 . Therefore, the spontaneous combustion of coal gangue is a process with the g factor value increasing, the free radical concentration rising, and the relaxation time lengthening (line width decreasing).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that TEMPO can combine with alkyl radicals to form inert substances, hinder the occurrence of free radical chain cycle reactions, and play a role in preventing the spontaneous combustion of coal. Wang 16 et al used N , N -dibenzylhydroxylamine (DBHA) as an inhibitor of spontaneous combustion of coal and conducted research and analysis. The results showed that DBHA can combine with hydrogen peroxide intermediates to form stable compounds, reduce the content of active free radicals in coal, and inhibit the spontaneous combustion of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al proposed an intumescent flame retardant, which can show good inhibitory effects during all stages of coal oxidation. Wang et al selected inorganic salt such as magnesium chloride and calcium chloride to combine with free radical scavengers N , N -dibenzylhydroxylamine and 2,6-di- tert -butyl-4-methylphenol to form a composite inhibitor. Christopher et al studied the effect of inorganic phosphate Pi and sulfonate mixed with surfactants on coal spontaneous combustion and found that inorganic salts can destroy free radicals generated during coal oxidation and surfactants can prevent coal from contacting with oxygen.…”
Section: Introductionmentioning
confidence: 99%